Self-assembly and characterization of transferrin–gold nanoconstructs and their interaction with bio-interfaces. Issue 17 (15th April 2015) - McDonagh, Birgitte H.; Volden, Sondre; Lystvet, Sina M.; Singh, Gurvinder; Ese, Marit-Helen G.; Ryan, Joseph A.; Lindgren, Mikael; Sandvig, Axel; Sandvig, Ioanna; Glomm, Wilhelm R.
Abstract : Transferrin (Tf) conjugated to gold nanoparticles and clusters combine the protein's site-specific receptor targeting capabilities with the optical properties imparted by the nano-sized gold. Abstract : Transferrin (Tf) conjugated to gold nanoparticles and clusters combine the protein's site-specific receptor targeting capabilities with the optical properties imparted by the nano-sized gold. We have described two different synthesis protocols, one yielding fluorescent Tf-stabilized gold nanoclusters (AuNCs) and one yielding Tf-stabilized gold nanoparticles that exhibit localized surface plasmon resonance. We demonstrate that the synthetic route employed has a large influence both on the gold nanostructure formed, and also on the structural integrity of the protein. A slight protein unfolding allows stronger interaction with lipids, and was found to significantly perturb lipid monolayers. Interactions between the protein–gold nanostructures and three different cell types were also assessed, indicating that the enhanced membrane affinity may be attributed to intercellular membrane differences.